2022
DOI: 10.1017/s147895152200092x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the feasibility, validity, and reliability of a screening tool for determining distress and supportive care needs of adolescents and young adults with cancer in Japan

Abstract: Objectives This study aims to (i) develop a screening tool for determining distress and supportive care needs of adolescent and young adult cancer patients (AYAs) based on the NCCN's Distress Thermometer and Problem List (DTPL), (ii) evaluate its feasibility, discriminant validity, and test–retest reliability in clinical settings, and (iii) report prevalence of distress and unmet needs. Method In the development phase, after translation of the Japanese version of the DTPL (DTPL-J) from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Over half of the women (57%) reported distress, which indicated the need for further evaluation and treatment. In their research with 230 adolescents and young adults with cancer in Japan, Hirayama et al (2022) found anxiety to be the most selected item on the NCCN DT problem list (36.6%). More referrals to psychological distress experts were made by nursing staff when distress was identified through use of the NCCN DT, meaning patients were more likely to receive the needed psychiatric care and psychological support.…”
Section: National Comprehensive Cancer Network Distress Thermometermentioning
confidence: 99%
“…Over half of the women (57%) reported distress, which indicated the need for further evaluation and treatment. In their research with 230 adolescents and young adults with cancer in Japan, Hirayama et al (2022) found anxiety to be the most selected item on the NCCN DT problem list (36.6%). More referrals to psychological distress experts were made by nursing staff when distress was identified through use of the NCCN DT, meaning patients were more likely to receive the needed psychiatric care and psychological support.…”
Section: National Comprehensive Cancer Network Distress Thermometermentioning
confidence: 99%
“…17 Furthermore, an AYA-specific screening tool based on the DTPL, Japanese version of the DTPL (DTPL-J), has been developed and validated for reliability as well as validity. 18 However, the DTPL-J covers a wide range of ages as well as new patients during the early phase of cancer; not limited to ACCS who have already completed inpatient treatment; the items of DTPL-J include family problems such as dealing with children and partners; and practical problems such as hospitalization life, money, childcare, and housing. The unique problems of ACCS aged 12-18 years after return to school such as academic and school-related problems, and interpersonal relationship have not been adequately measured by DTPL-J.…”
Section: Development Of Adolescent Childhood Cancer Survivors' Psycho...mentioning
confidence: 99%
“…The DTPL has been reported to be useful for identifying clinically psychological distress in adolescents and young adults (AYA) aged 15–39 years old during the early phases of their cancer 17 . Furthermore, an AYA‐specific screening tool based on the DTPL, Japanese version of the DTPL (DTPL‐J), has been developed and validated for reliability as well as validity 18 . However, the DTPL‐J covers a wide range of ages as well as new patients during the early phase of cancer; not limited to ACCS who have already completed inpatient treatment; the items of DTPL‐J include family problems such as dealing with children and partners; and practical problems such as hospitalization life, money, childcare, and housing.…”
Section: Introductionmentioning
confidence: 99%